Lack of efficacy of AMP against recrudescent genital herpes infections in guinea pigs. - Fraser-Smith, E B (1983)
AMP was evaluated for its efficacy against herpes simplex virus type 2 genital infections in guinea pigs. Vaginally infected animals were treated twice a day with AMP at 50 mg/kg per dose for 2 weeks. Subcutaneous doses were started 10 weeks postinfection. AMP treatment did not reduce the number of animals with recrudescent episodes when compared with saline-treated controls. In addition, AMP treatment did not reduce either the number of lesions or the duration of the recrudescent episodes which did develop. These results suggest that AMP has no effect on recrudescent herpes simplex virus type 2 vaginal infections.